Hodnocení prvního roku existence datových schránek - Lechner, Tomáš (Univerzita Pardubice, 2010)
The paper deals with data boxes information system as the new electronic public service created within the e-Government in the Czech Republic. First there is presented development of electronic communications in public administration, which resulted in the introduction of this new e-Government tool. Evaluation of the first year of the data boxes is done from four angles: from the perspective of implementation of data boxes information system, from the perspective of legal impacts, from the perspective of changes of processes and from the perspective of economic impacts.
Keywords: e-Government; data boxes; public administration in the Czech Republic